Answer:
I rlly don’t k srry
I be getting stuck to
Step-by-step explanation:
On a graph, an exponential growth is shown as a line going up as you go from left to write. In an equation, exponential growth is shown if the b part of y=ab^x is greater than one.
-4(3)=-12
-4(6)=-24
-12+(-24)=-36
Answer:
I don't see any thing there
Step-by-step explanation:
u need to include the picture
Answer:
x = -6 x= -3
Step-by-step explanation:
f(x) = x^2+9x+18
Set equal to 0 to find the zeros
0 = x^2+9x+18
Factor, what numbers multiply to 18 and add to 9
6*3 =18
6+3=9
0= (x+6) (x+3)
Using the zero product property
x+6 =0 x+3 =0
x = -6 x= -3